Space use and microhabitat selection of wild giant pandas in Meigu Dafengding National Nature Reserve, China - Chen, Yuxiang; Wang, Xiao; Zheng, Xiaoguang; Gong, Yihua; Chen, Minghua; Qiu, Lan; Zhou, Hong; Wei, Wei; Han, Han (Frontiers in Ecology and Evolution, 2022)
The giant panda (Ailuropoda melanoleuca) is a special rare and endangered species in China and is the flagship species for global biodiversity conservation. This study used different methods including Kernel density, statistical analysis, and logistic regression analysis to investigated the spatial distribution, migration in different seasons and different distribution areas, as well as the foraging patch selection strategies of wild giant pandas in Meigu Dafengding National Nature Reserve in the Liangshan Mountains. The results demonstrated that, in the study area, giant pandas were mainly distributed in the Wahei-Yizi Yakou Habitat Corridor with an activity area of 144.93 km2, which accounted for 28.59% of the whole reserve. The core distribution area of the species was 92.07 km2 and the population density was 0.24 pcs km–2. There were two significant seasonal domains for the activities of giant pandas: the low-altitude winter habitat of Yushania maculata Yi and Yushania ailuropodina Yi bamboo species, as well as the high-altitude summer habitat of Bashania fangiana species. With seasonal changes, giant pandas migrated among different bamboo distribution regions. Giant pandas were mainly distributed in high-altitude areas that had secondary forest, tall trees with a large diameter at breast height (DBH) and bamboo forest. The spatial distribution pattern and microhabitat selection of giant pandas in Meigu Dafengding National Nature Reserve were determined. The findings of this study provide scientific implications for the local conservation and management of the habitat of wild giant pandas.